Forms of epithelial differentiation of draining sinus in acne inversa (hidradenitis suppurativa) - Kurzen, Hjalmar; Jung, Ernst G.; Hartschuh, Wolfgang; Franke, Werner (British journal of dermatology, 2001)
The draining sinus is a late complication of several forms of severe acne, leading to extensive, periodically inflamed lesions that are undermined by a system of fistulas, supposed to be of follicular origin.
Elektronische Reproduktion der Druck-Ausgabe
First published: 24 December 2001
Gesehen am 11.02.2021